2021
DOI: 10.1186/s12889-021-10638-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of injury severity on long-term outcomes following motor vehicle crashes

Abstract: Background There is growing evidence that a range of pre-injury, injury related and post-injury factors influence social and health outcomes across the injury severity spectrum. This paper documents health related outcomes for people with mild, moderate and severe injury after motor vehicle crash (MVC) injuries in New South Wales, Australia. Methods This inception cohort study followed 2019 people injured in MVCs, for 6 and 12 months post-injury. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Secondly, despite LOS being the most common indicator for injury severity used by transportation authorities worldwide ( 17 ), critics have argued that LOS will depend on comorbidity factors and also be affected by changes in healthcare delivery over time ( 40 ). However, from our previous analyses using the same dataset, it was found that the LOS and Injury Severity Score were strongly related, supporting the use of LOS in this study ( 16 ). The DASS21, IESR and Pain Catastrophizing Scale were chosen for this study because of the excellent criterion validity for detecting these psychological disorders in injured participants ( 23 ); nonetheless they are not intended for the purposes of diagnosis of psychological disorder and not comparable to clinical diagnosis by mental health professionals.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Secondly, despite LOS being the most common indicator for injury severity used by transportation authorities worldwide ( 17 ), critics have argued that LOS will depend on comorbidity factors and also be affected by changes in healthcare delivery over time ( 40 ). However, from our previous analyses using the same dataset, it was found that the LOS and Injury Severity Score were strongly related, supporting the use of LOS in this study ( 16 ). The DASS21, IESR and Pain Catastrophizing Scale were chosen for this study because of the excellent criterion validity for detecting these psychological disorders in injured participants ( 23 ); nonetheless they are not intended for the purposes of diagnosis of psychological disorder and not comparable to clinical diagnosis by mental health professionals.…”
Section: Discussionsupporting
confidence: 86%
“…Participants were divided into 3 groups of injury severity according to their self-reported length of hospital stay (LOS), with mild injury defined as participants with LOS of 1 day or less (including participants who did not present or who were not admitted to hospital), moderate for participants with LOS 2–6 days and severe with LOS ≥ 7 days. The use of LOS as injury severity measure has been common practice ( 17 ) and this LOS cut-off has been reported previously (and is strongly correlated with Injury Severity Score) ( 16 ). Participants were assessed using a structured interview at baseline, and again at 6 and 12 months after injury.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Injury severity was also evaluated using the Injury Severity Scale (ISS), derived from Abbreviated Injury Scale scores of affected body regions [ 33 ]. Injury Severity Scale scores were derived by a trained coder using methods and injury data sources described by Hung et al [ 34 ]. Participant-perceived danger of death during the crash was evaluated on a 5-point Likert scale (0-none to 5-overwhelming).…”
Section: Methodsmentioning
confidence: 99%
“…Chassé M et al showed that higher BMI in women may be a risk factor [2]. Ntundu SH et al further showed that blunt abdominal injury was commonly linked to road traffic accidents (RTAs) [3][4][5][6][7][8][9][10]. Mortality was linked to extra-abdominal injury, injury to the head or pelvis, length of stay (LOS) ≥ seven days, systolic BP < 90, and anemia.…”
Section: Introductionmentioning
confidence: 99%